A Statistical Analysis of College Students Academic Performance: A Case Study of Amrit Campus - Nepal, Surendra Raj; Pradhan, Bijay Lal (Amrit Research Journal, 2022)
Every Universities/Colleges want their more students are able to pass their exams. That is why they are looking for effective policies and programs. This study helps them to make new policies for the betterment of the students and change inefficient old policies if any in their Universities/Colleges. This investigation’s purpose is to evaluate the consequences of gender, level, group and system on students’ academic performance by taking students in Amrit Campus. After analyzing through chi-square and logistic regression, it is found that except gender other three variables have significant impact on performance. The performance of biological group students is better than physical group students. Likewise, bachelor level students have performed well as compared to master level. Additionally, semester students pass at a higher rate than those enrolled in the yearly system. Among various combinations of bachelor level, EBC (Environment, Botany, and Chemistry) and among Master level Zoology students are more serious about their exam.